2002
DOI: 10.1007/s12043-002-0179-0
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization study of mercurocuprate (Hg,Re)Sr2CuO4+δ

Abstract: The nominal (Hg 1−x Re x )Sr 2 CuO 4+δ (x = 0.10 and 0.20) samples were synthesized at ∼ 920 • C in partial vacuum. The compound with x =0.10 exhibits superconductivity at ∼ 54 K while the composition x = 0.20 is non-superconducting down to 5 K. On cooling below 10 K in an applied field of 4 kOe, the former causes a noticeable upturn in the field cooled (FC) magnetization signal. Such a change in magnetic response is also reflected in the magnetic hysteresis loop generated at 9 K. We attribute this effect to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…They showed that the Ba-free mercurocuprate (Hg 0.8 Re 0.2 )Sr 2 CuO 4+δ was significantly more thermally stable than HgBa 2 CuO 4+δ , allowing heat treatments at temperatures of at least 1073 K for moderate periods of time and with only very minor decomposition observed. More recently, we reported that samples of nominal (Hg 1−x Re x )Sr 2 CuO 4+δ (x = 0.05, 0.10 and 0.20) compositions, synthesized in partial vacuum at 1193 K for 16-32 h [80][81][82], show that x = 0.05 and 0.10 are superconducting (SC) with T onset c ∼ 40 and ∼54 K, respectively, while the x = 0.20 composition is non-SC down to 5 K [81]. The computed lattice parameters given in table 8 show a slight decrease in the values with a progressive increase in x from 0.05 to 0.20.…”
Section: (Hg Re)sr 2 Cuo 4+δ Systemmentioning
confidence: 99%
“…They showed that the Ba-free mercurocuprate (Hg 0.8 Re 0.2 )Sr 2 CuO 4+δ was significantly more thermally stable than HgBa 2 CuO 4+δ , allowing heat treatments at temperatures of at least 1073 K for moderate periods of time and with only very minor decomposition observed. More recently, we reported that samples of nominal (Hg 1−x Re x )Sr 2 CuO 4+δ (x = 0.05, 0.10 and 0.20) compositions, synthesized in partial vacuum at 1193 K for 16-32 h [80][81][82], show that x = 0.05 and 0.10 are superconducting (SC) with T onset c ∼ 40 and ∼54 K, respectively, while the x = 0.20 composition is non-SC down to 5 K [81]. The computed lattice parameters given in table 8 show a slight decrease in the values with a progressive increase in x from 0.05 to 0.20.…”
Section: (Hg Re)sr 2 Cuo 4+δ Systemmentioning
confidence: 99%